2017
DOI: 10.1038/nmeth.4258
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor T-cell differentiation from hematopoietic stem cells using Delta-like-4 and VCAM-1

Abstract: The molecular and cellular signals that guide T-cell development from hematopoietic stem and progenitor cells (HSPCs) remain poorly understood. The thymic microenvironment integrates multiple niche molecules to potentiate T-cell development in vivo. Recapitulating these signals in vitro in a stromal cell-free system has been challenging and limits T-cell generation technologies. Here, we describe a fully defined engineered in vitro niche capable of guiding T-lineage development from HSPCs. Synergistic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 53 publications
1
106
0
Order By: Relevance
“…VCAM-1 contributes to stromal-DN3 interactions and its presence is associated with improved in vitro generation of T cells (Abe et al, 2010;Shukla et al, 2017). We therefore assessed the impact of Fc-VCAM-1 on DL4-mediated polarisation during division by functionalising the surfaces with both ligands.…”
Section: Notch Functionally Interacts With Other Cues To Orchestrate Acdmentioning
confidence: 99%
See 1 more Smart Citation
“…VCAM-1 contributes to stromal-DN3 interactions and its presence is associated with improved in vitro generation of T cells (Abe et al, 2010;Shukla et al, 2017). We therefore assessed the impact of Fc-VCAM-1 on DL4-mediated polarisation during division by functionalising the surfaces with both ligands.…”
Section: Notch Functionally Interacts With Other Cues To Orchestrate Acdmentioning
confidence: 99%
“…Notch signalling is required for progression through β-selection and subsequent fate choices (Ciofani et al, 2004;Ciofani et al, 2005). We exploited two model systems to explore the role of Notch1 during division of developing T cells; the OP9-DL1 coculture, and surfaces functionalised with Fc-DL1 (Janas et al, 2010;Mohtashami et al, 2010;Schmitt et al, 2002;Shukla et al, 2017;Van de Walle et al, 2013). We show that the interaction of Notch1 with its ligands, DL1 and DL4, drives the polarisation of Notch1 itself, and consequently the polarisation of cell fate determinants, α-Adaptin and Numb.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70][71][72][73] Stromal-free cell culture systems are emerging. 74 Thus, Notch-based culture systems may offer an opportunity to generate naïve T cells for cell-based immunotherapies. Several reports have demonstrated the efficient generation and therapeutic potential of T-cell precursors generated by Notchbased culture of hematopoietic progenitor cells.…”
Section: Lymphoid Progenitor Car Therapymentioning
confidence: 99%
“…More recently, Zúñiga‐Pflücker and coworkers developed a more defined coculture system based on the critical function of the Notch pathway in T cell development. Studies using hematopoietic progenitor cells isolated from different sources demonstrated that overexpressing Notch ligand Delta‐like‐1 (OP9‐DL1) or Delta‐like‐4 (OP9‐DL4) expressed by mouse bone marrow‐derived OP9 stromal cells provides a suitable microenvironment to initiate T lymphopoiesis . These studies have used cells from human fetal liver , human umbilical cord blood (UCB) , and mouse ESC‐derived hematopoietic cells .…”
Section: Making T Cells In a Dishmentioning
confidence: 99%
“…Studies using hematopoietic progenitor cells isolated from different sources demonstrated that overexpressing Notch ligand Delta‐like‐1 (OP9‐DL1) or Delta‐like‐4 (OP9‐DL4) expressed by mouse bone marrow‐derived OP9 stromal cells provides a suitable microenvironment to initiate T lymphopoiesis . These studies have used cells from human fetal liver , human umbilical cord blood (UCB) , and mouse ESC‐derived hematopoietic cells . The in vitro‐derived CD8 + SP T cells exhibit standard pathway activation upon stimulation and are capable of killing specific target cells if engineered with CAR and TCR .…”
Section: Making T Cells In a Dishmentioning
confidence: 99%